Addressing the Loophole for Juvenile Status Offenses - Magee, Gregory (Eximia, 2024)
Juvenile status offenses were created to protect against unnecessary physical detention of juveniles. Petty actions by teenagers are expected. Researchers have found that physically detaining juveniles in detention centers for behaviors such as truancy, running away, etc., did more harm than good. The Juvenile Justice and Delinquency Prevention Act of 1974 was enacted to create guidelines and prevent unnecessary detainment of juveniles. An amendment to the act in 1980 allowed judges to detain juveniles regarding status offenses if specific criteria were met. What seemed to be a minor change sought to protect juveniles from their own unruly conduct, i.e., running away or violating a court order. Ultimately, discretion to detain a juvenile began to be used very often. The undermining of status offenses has gained attention from many officials. The North Dakota Governor, Doug Burgum, did not hesitate to sign House Bill 1035 when it was made available to his office. The bill addresses the loophole, though the benefit has yet to be measured.